2013
DOI: 10.2174/157340313805076313
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Lifestyle Modification in the Management of Hypercholesterolemia

Abstract: Background:Coronary heart disease (CHD) is the leading cause of morbidity and mortality worldwide. The growth of ageing populations in developing countries with progressively urbanized lifestyles are major contributors. The key risk factors for CHD such as hypercholesterolemia, diabetes mellitus, and obesity are likely to increase in the future. These risk factors are modifiable through lifestyle. Objectives: To review current literature on the potential benefit of cholesterol lowering in CHD risk reduction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 118 publications
3
59
0
1
Order By: Relevance
“…Longitudinal follow-up studies of the patients with CVDs have demonstrated that there are likely declines in lipid profiles following training program (18). In the present study, it was seen that following 8-week exercise programs, the mean apoA-I levels significantly increased as well as HDL-C in EG and RG.…”
Section: Discussionsupporting
confidence: 46%
“…Longitudinal follow-up studies of the patients with CVDs have demonstrated that there are likely declines in lipid profiles following training program (18). In the present study, it was seen that following 8-week exercise programs, the mean apoA-I levels significantly increased as well as HDL-C in EG and RG.…”
Section: Discussionsupporting
confidence: 46%
“…Although the reasons for change in cholesterol levels cannot be determined, we can assume that such decrease would be achieved mostly by statin medication or lifestyle intervention. Well‐established lifestyle management includes diet, increased physical activity, and weight control 24, 25. However, only 10% to 42% of young adults meet the optimal physical activity levels recommended26, 27 and the prevalence of obesity among young adults is persistently increasing not only in Korea28 but also globally 29.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these findings, the effect of self-management on medical risk factors was not significant. The efficacy of lifestyle modification at improving blood pressure [46][47]and glucose control [48], as well as lowering cholesterol [49] is well established. A path in which lifestyle behaviour modification precedes changes to medical conditions is thus implied and represents a plausible explanation as to why a significant effect was observed on lifestyle behaviour but not medical risk factors.…”
Section: Discussionmentioning
confidence: 99%